Exposed high-strength single-component waterproof coating and preparation method thereof
By selecting pure acyl emulsion and zinc oxide with a specific glass transition temperature in a single-component waterproof coating, the problem of reducing adhesion and tensile strength of existing coatings under the influence of weather is solved, and a high-strength and high elongation coating is achieved, and good water resistance and weather resistance are provided.
Patent Information
- Application Number
- CN202411858609.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-03-25
AI Technical Summary
After the influence of sunlight and rainwater erosion, the adhesion and tensile strength of the paint film to the substrate is significantly reduced, resulting in cracks and settlement on the surface of the paint film, and cracks gradually appear on the wall.
By selecting pure acrylic emulsion A and pure acrylic emulsion B with glass transition temperatures of -10℃~0℃ and -45℃~-30℃, respectively, combined with zinc oxide and silicone modified pure acrylic emulsion, the composition and process flow of the coating are adjusted, and a exposed high-strength single-component waterproof coating is prepared.
The formed coating has high tensile strength, high elongation of fracture, and has good water resistance and weather resistance, which is not easy to crack or fall off due to erosion of the natural environment.
Smart Images

Figure BDA0005192808950000041 
Figure BDA0005192808950000051 
Figure BDA0005192808950000061
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of coatings, and in particular to an exposed high-strength single-component waterproof coating and a preparation method thereof. Background Art
[0002] With the development of the times and the advancement of science and technology, the modern construction industry has developed rapidly, and people's requirements for coatings have also risen. Coatings are an important part of construction projects, which can play a role in protection and decoration. At the same time, as people's demand for high-quality life gradually increases, people's requirements for coatings are also becoming more and more important.
[0003] The paint film formed by the single-component waterproof coatings currently on the market has a high elongation, but the tensile strength is generally low. Moreover, after being exposed to sunlight, rain and other weather influences, the adhesion and tensile strength of the paint film to the substrate are significantly reduced, resulting in cracking and settlement on the surface of the paint film, and cracks will gradually appear on the wall.
[0004] Therefore, it is necessary to seek a one-component waterproof coating so that the coating prepared therefrom has both high tensile strength and high elongation at break. Summary of the invention
[0005] The object of the present invention is to provide an externally exposed high-strength single-component waterproof coating and a preparation method thereof, wherein the coating prepared by the externally exposed high-strength single-component waterproof coating has both high tensile strength and high elongation at break.
[0006] According to one aspect of the present invention, there is provided an exposed high-strength single-component waterproof coating. Calculated by weight, the raw materials for preparing the exposed high-strength single-component waterproof coating include: 350 to 450 parts of pure acrylic emulsion A, 150 to 250 parts of pure acrylic emulsion B, 250 to 350 parts of powder, 13.5 to 39 parts of additives, and 50 to 110 parts of aqueous solvent; wherein the glass transition temperature of pure acrylic emulsion A is -10°C to 0°C, and the glass transition temperature of pure acrylic emulsion B is -45°C to -30°C.
[0007] By selecting two pure acrylic emulsions whose glass transition temperatures meet the above ranges to prepare the exposed high-strength single-component waterproof coating, the formed coating can have high tensile strength, high elongation at break, good water resistance and weather resistance. On the one hand, the glass transition temperature (Tg) of the emulsion refers to the temperature at which the molecular polymer in the emulsion changes from an elastic state to a glass state, and by regulating the glass transition temperatures of pure acrylic emulsion A and pure acrylic emulsion B within the above range, the tensile strength and elongation of the coating formed by the exposed high-strength single-component waterproof coating can be improved at the same time. On the other hand, by selecting pure acrylic emulsion A and pure acrylic emulsion B, which are polymerized from monomers such as acrylates, the weather resistance and water resistance of the coating formed by the exposed high-strength single-component waterproof coating can be improved, and it is not easy to oxidize, yellow or even degrade and age, and the tensile strength and elongation of the coating after being washed by rainwater are both within the excellent range. That is to say, the coating can be directly exposed to the external environment and is not easy to crack or fall off due to erosion by natural environments such as sunlight, rain, and temperature changes. Therefore, the high-strength single-component waterproof coating that can be exposed can be applied to the roof and exterior walls of buildings. In addition, it should be noted that in the coating formed by conventional single-component waterproof coatings, when the coating has a higher tensile strength, its elongation at break is lower; when the coating has a higher elongation at break, its tensile strength is lower.
[0008] Preferably, the pure acrylic emulsion A includes an organosilicon-modified pure acrylic emulsion, and the organosilicon content of the organosilicon-modified pure acrylic emulsion is 1 to 2 wt%. By adopting the above-mentioned organosilicon-modified pure acrylic emulsion as the pure acrylic emulsion A, the water resistance and adhesion of the coating formed by the exposed high-strength single-component waterproof coating can be further improved. First, since the organosilicon-modified pure acrylic emulsion has a higher cohesive strength than the unmodified pure acrylic emulsion, the adhesion of the coating is improved, and the aging resistance of the coating is improved, which is conducive to the coating to withstand the erosion of the natural environment. Secondly, adding the organosilicon-modified pure acrylic emulsion to the coating system can introduce an organosilicon structure into the coating, so that when the coating is cured to form a film, as the aqueous solvent evaporates, the organosilicon structure in the coating migrates to the surface of the coating, so that the prepared coating has a lower surface energy and a larger water contact angle, and it is difficult for rainwater or dirt to stay on the surface of the coating, so that the coating has good water resistance.
[0009] Preferably, the additive includes 2 to 10 parts of zinc oxide, calculated by weight. By introducing zinc oxide into the coating system, the compactness of the coating formed by the exposed high-strength single-component waterproof coating can be improved, the water absorption rate of the coating can be reduced, and the waterproof and water-resistant properties and aging resistance of the coating can be improved. By utilizing the complexation between zinc oxide and the carboxyl groups of pure acrylic emulsion A and pure acrylic emulsion B, an inorganic-organic three-dimensional network structure is formed inside the coating. The three-dimensional network structure also gives the coating excellent deformation resistance and elasticity, thereby improving the toughness and strength of the coating. Among them, compared with pure acrylic emulsion B, pure acrylic emulsion A with a higher glass transition temperature contains more carboxyl functional groups, so there is a stronger complexation between pure acrylic emulsion A and zinc oxide, and the complexation reaction activity is higher. By adjusting the feeding amount of zinc oxide in combination with the feeding amount of pure acrylic emulsion A and pure acrylic emulsion B in the exposed high-strength one-component waterproof coating, the film density of the exposed high-strength one-component waterproof coating can be further improved, and the tensile strength and elongation at break of the coating formed can be balanced.
[0010] Preferably, the pH value of the exposed high-strength single-component waterproof coating is 7.5 to 8.5. By adjusting the pH value of the coating system to the above range, it is beneficial to promote the complex reaction between zinc oxide and pure acrylic emulsion A and pure acrylic emulsion B, improve the crosslinking degree of the inorganic-organic three-dimensional network structure, and improve the film-forming stability and film-forming density of the exposed high-strength single-component waterproof coating.
[0011] Preferably, the pure acrylic emulsion A is an emulsion product produced by Badfu with a brand name of FS-6733.
[0012] Preferably, the pure acrylic emulsion B is an emulsion product produced by Badfu with a brand name of FS-7830.
[0013] Preferably, the powder includes at least one of calcium carbonate, barium sulfate, titanium dioxide and talc.
[0014] Preferably, the calcium carbonate comprises ground calcium carbonate.
[0015] Preferably, the additive includes 0.5 to 1.5 parts of cellulose ether by weight. By introducing cellulose ether into the coating system, it is beneficial to control the viscosity and dispersion characteristics of the coating system, so that the powder particles of the above amount can be evenly suspended in the coating system during the storage and drying process of the coating, so as to improve the storage stability and coating uniformity of the coating.
[0016] Preferably, the cellulose ether is hydrophobically modified hydroxyethyl cellulose ether. By selecting hydrophobically modified hydroxyethyl cellulose ether, the compatibility of cellulose ether with the coating system can be further improved, and the fluidity and leveling of the coating can be better improved.
[0017] Optionally, the cellulose ether includes at least one of a product with a brand number of HE-10K, a product with a brand number of 481FQ, and a product with a brand number of plus330.
[0018] Preferably, calculated by weight, the auxiliary agent includes 2 to 6 parts of sodium salt dispersant.
[0019] Optionally, the sodium salt dispersant is a hydrophobically modified sodium salt dispersant.
[0020] Optionally, the dispersant includes at least one of a dispersant with a brand number of SN-5040, a dispersant with a brand number of 731A, and a dispersant with a brand number of CA2500.
[0021] Preferably, calculated by weight, the auxiliary agent includes 1 to 5 parts of a plasticizer, and the plasticizer includes at least one of phthalate esters and aliphatic dibasic acid esters.
[0022] Preferably, the viscosity of the exposed high-strength single-component waterproof coating is 100-110 KU. Adjusting the viscosity of the exposed high-strength single-component waterproof coating to the above range is beneficial to improving the storage stability of the coating, reducing the possibility of powder sedimentation in the coating system, and also beneficial to improving the adhesion and durability of the coating, improving the construction performance, making the coating better adhere to the wall surface, and improving the covering power and aesthetics of the coating.
[0023] Preferably, the aqueous solvent is deionized water.
[0024] Preferably, the auxiliary agent includes at least one of a wetting agent, a pH regulator, a defoaming agent, a thickener, and a bactericide.
[0025] According to another aspect of the present invention, there is provided a method for preparing the above-mentioned exposed high-strength single-component waterproof coating, comprising the following operations:
[0026] Firstly, pure acrylic emulsion A and pure acrylic emulsion B are mixed with an aqueous solvent to obtain a premixed liquid, and then the premixed liquid is mixed with the remaining raw materials to obtain an exposed high-strength single-component waterproof coating. DETAILED DESCRIPTION
[0027] In order to enable those skilled in the art to better understand the technical solutions of the present invention, the technical solutions of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
[0028] Example 1
[0029] This embodiment provides a high-strength single-component waterproof coating that can be exposed, consisting of the following components:
[0030] Table 1. Raw material composition of the high-strength single-component waterproof coating in Example 1
[0031]
[0032]
[0033] Among them, the emulsion product with the brand name FS-6733 produced by Badfu is a pure acrylic emulsion modified with silicone, with a silicone content of 1 to 2 wt% and a glass transition temperature of -10°C to 0°C. The emulsion product with the brand name FS-7830 produced by Badfu is a pure acrylic emulsion with a glass transition temperature of -45°C to -30°C. The above-mentioned cellulose ether is a product with the brand name plus330 produced by Ashland, and the sodium salt dispersant is a dispersant with the brand name SN-5040 produced by Nopco.
[0034] The preparation method of the exposed high-strength single-component waterproof coating is as follows:
[0035] S1. First, pure acrylic emulsion A, pure acrylic emulsion B and aqueous solvent are mixed evenly to obtain a premixed solution;
[0036] S2. The premixed liquid is then mixed with the cellulose ether, dispersed, and the dispersion rate is gradually increased according to the viscosity of the coating system until the cellulose ether is fully dissolved;
[0037] S3. Add sodium salt dispersant, wetting agent, pH adjuster and defoamer to the coating system and continue to disperse for 8 minutes;
[0038] S4. Add zinc oxide and powder to the coating system and disperse at high speed for 25 minutes; then add defoamer, plasticizer and fungicide to the coating system and mix well;
[0039] S5. Then, a thickener is added to the coating system, the viscosity of the coating system is adjusted to within the range of 100 to 105 KU, and the pH of the coating system is controlled within the range of 7.5 to 8.5, so as to obtain an exposed high-strength single-component waterproof coating.
[0040] In other embodiments, the type and amount of the aqueous solvent are adjusted, or the type and amount of the additive are adjusted, or the order of feeding, stirring speed, dispersion time, etc. in the preparation process are adjusted. The premise is that it does not affect the normal use of the exposed high-strength single-component waterproof coating.
[0041] Example 2
[0042] This example refers to the preparation method provided in Example 1 to prepare an exposed high-strength single-component waterproof coating. The difference between this example and Example 1 is that in the process of preparing the exposed high-strength single-component waterproof coating, a pure acrylic emulsion with the brand name FS-9900 produced by Badfu Company of equal quality is used to replace the pure acrylic emulsion A in Example 1. The glass transition temperature of the emulsion product is -10 to 0°C, and the emulsion product has not been modified with organic silicon. The rest of the raw material ratios and preparation methods are strictly consistent with those in Example 1.
[0043] Example 3
[0044] This example refers to the preparation method provided in Example 1 to prepare an externally exposed high-strength single-component waterproof coating. The difference between this example and Example 1 is that the raw materials used to prepare the externally exposed high-strength single-component waterproof coating are adjusted as shown in Table 2, and the viscosity of the coating system is adjusted to 110KU. The remaining raw material ratios and preparation methods are strictly consistent with those in Example 1.
[0045] Table 2. Raw material composition of the high-strength single-component waterproof coating in Example 3
[0046]
[0047] Example 4
[0048] This example refers to the preparation method provided in Example 1 to prepare an exposed high-strength single-component waterproof coating. The difference between this example and Example 1 is that the raw materials used to prepare the exposed high-strength single-component waterproof coating are adjusted as shown in Table 3, and the viscosity of the coating system is adjusted to 105KU. The remaining raw material ratios and preparation methods are strictly consistent with those in Example 1.
[0049] Table 3. Raw material composition of the high-strength single-component waterproof coating in Example 4
[0050]
[0051] Comparative Example 1
[0052] This example prepares a coating with reference to the preparation method provided in Example 1. The difference between this example and Example 1 is that in the process of preparing the coating, pure acrylic emulsion A of equal mass is used to replace pure acrylic emulsion B in Example 1. In other words, the coating only uses pure acrylic emulsion A. The rest of the raw material ratios and preparation methods are strictly consistent with those in Example 1.
[0053] Comparative Example 2
[0054] This example prepares a coating with reference to the preparation method provided in Example 1. The difference between this example and Example 1 is that in the process of preparing the coating, pure acrylic emulsion B of equal mass is used to replace pure acrylic emulsion A in Example 1. In other words, the coating only uses pure acrylic emulsion B. The rest of the raw material ratios and preparation methods are strictly consistent with those in Example 1.
[0055] Comparative Example 3
[0056] This example prepares a coating with reference to the preparation method provided in Example 1. The difference between this example and Example 1 is that in the process of preparing the coating, pure acrylic emulsion RS-9689A produced by Badford Company of equal quality is used to replace pure acrylic emulsion B in Example 1. The glass transition temperature of the emulsion product is -25°C to -15°C. The other raw material ratios and preparation methods are strictly consistent with those in Example 1.
[0057] Comparative Example 4
[0058] This example is used to prepare a coating by referring to the preparation method provided in Example 1. The difference between this example and Example 1 is that in the process of preparing the coating, a styrene-acrylic emulsion of the same quality and the grade FS-7681 produced by Badfu Company is used to replace the pure acrylic emulsion B in Example 1. The other raw material ratios and preparation methods are strictly consistent with those in Example 1.
[0059] Test Example 1
[0060] Test objects: the exposed high-strength single-component waterproof coating provided in Examples 1 to 4, and the coating provided in Comparative Examples 1 to 4.
[0061] Test items and methods:
[0062] (1) Tensile properties: Under the experimental conditions of ambient temperature (23±2)°C and relative humidity (50±5)%, the test objects were made into coatings according to the method provided in JC / T 864-2008 Polymer Emulsion Waterproof Coatings for Buildings, cut, and tested the untreated tensile properties of the coatings according to the method 8.2.2 in GB / T 16777-1997 Test Methods for Waterproof Coatings for Buildings. The tensile speed was 200 mm / min.
[0063] The tensile strength and elongation at break of the coating were recorded respectively. The test results of tensile strength were expressed as the arithmetic mean of 5 samples; the test results of elongation at break were expressed as the arithmetic mean of 5 samples.
[0064] (2) Tensile properties after artificial weathering: Referring to JC / T 864-2008 Polymer Emulsion Building Waterproof Coating, the test object was made into a coating and subjected to a xenon arc lamp aging test chamber as required in Chapter 6 of GB / T 18244-2000 Test Method for Aging of Building Waterproof Materials. The cumulative irradiation energy of the test was 1500 MJ / m 2 Then take it out after aging (about 720 hours). Then place the coating in an experimental environment with an ambient temperature of (23±2)℃ and a relative humidity of (50±5)% for 4 hours, cut it, and then refer to the method 8.2.2 in "GB / T 16777-1997 Test Methods for Building Waterproof Coatings" to test the tensile properties of the coating after aging treatment, with a tensile speed of 200mm / min.
[0065] The tensile strength and elongation at break of the coating after aging treatment were recorded respectively, and the tensile strength retention rate of the coating was calculated. The test results of tensile strength were expressed as the arithmetic mean of 5 samples; the test results of elongation at break were expressed as the arithmetic mean of 5 samples.
[0066] The calculation formula of the tensile strength retention rate is: tensile strength retention rate = (tensile strength after aging treatment / tensile strength without treatment) × 100%.
[0067] Test results: The test results of the above tests are shown in Table 4.
[0068] Table 4. Test properties of coatings prepared by each test object
[0069]
[0070] Result analysis:
[0071] By comparing the coatings and performance indicators provided by Examples 1 to 4 with those provided by Comparative Examples 1 to 4, it can be found that the tensile strength of the coatings provided by Examples 1 to 4 before aging treatment is ≥ 2.72 MPa, and the elongation at break before aging treatment is > 157.16%. The comprehensive performance of the coatings provided by Examples 1 to 4 is better than that of the coatings provided by Comparative Examples 1 to 4.
[0072] By comparing the performance of the coating provided by Example 1 with that provided by Comparative Examples 1 to 2, it can be found that the coating prepared by Example 1 using both pure acrylic emulsion A and pure acrylic emulsion B has both high tensile strength and high elongation at break. Among them, the coating provided by Comparative Example 1 uses only pure acrylic emulsion A with a glass transition temperature of -10°C to 0°C. Although the prepared coating exhibits high tensile strength, the elongation at break of the coating is poor. The coating provided by Comparative Example 2 uses only pure acrylic emulsion B with a glass transition temperature of -45°C to -30°C. Although the prepared coating exhibits good elongation at break, the tensile strength of the coating is poor. Further, by comparing the coating provided by Example 1 with that provided by Comparative Examples 3 to 4, it can be found that when pure acrylic emulsion B with a glass transition temperature of -45°C to -30°C and pure acrylic emulsion A with a glass transition temperature of -10°C to 0°C are used to prepare the coating, the tensile strength and elongation of the coating can be improved at the same time. In addition, during the aging test, it was found that the coating provided in Comparative Example 4 was prone to yellowing, and the color retention of the coating under ultraviolet light, in particular, needed to be improved.
[0073] Example 5
[0074] This embodiment refers to the preparation method provided in Example 1 to prepare an externally exposed high-strength single-component waterproof coating. The difference between this embodiment and Example 1 is that in the process of preparing the externally exposed high-strength single-component waterproof coating, an aqueous solvent of equal mass is used to replace zinc oxide. In other words, the raw material does not contain zinc oxide. The rest of the raw material ratios and preparation methods are strictly consistent with those in Example 1.
[0075] Example 6
[0076] This embodiment refers to the preparation method provided in Example 1 to prepare an externally exposed high-strength single-component waterproof coating. The difference between this embodiment and Example 1 is that in the process of preparing the externally exposed high-strength single-component waterproof coating, the amount of oxidizing agent and aqueous solvent added is adjusted so that the raw material includes 2 parts of zinc oxide. The remaining raw material ratios and preparation methods are strictly consistent with those in Example 1.
[0077] Example 7
[0078] This example refers to the preparation method provided in Example 1 to prepare an externally exposed high-strength single-component waterproof coating. The difference between this example and Example 1 is that in the process of preparing the externally exposed high-strength single-component waterproof coating, the amount of oxidizing agent and aqueous solvent added is adjusted so that the raw material includes 10 parts of zinc oxide. The remaining raw material ratios and preparation methods are strictly consistent with those in Example 1.
[0079] Comparative Example 5
[0080] This comparative example refers to the preparation method provided in Example 1 to prepare a coating. The difference between this comparative example and Example 1 is that in the process of preparing the coating, an equal mass of pure acrylic emulsion B is used to replace the pure acrylic emulsion A in Example 1, and an equal mass of aqueous solvent is used to replace zinc oxide. In other words, the coating only uses pure acrylic emulsion B, and the raw materials do not contain zinc oxide. The rest of the raw material ratios and preparation methods are strictly consistent with those in Example 1.
[0081] Comparative Example 6
[0082] This comparative example refers to the preparation method provided in Example 1 to prepare a coating. The difference between this comparative example and Example 1 is that in the process of preparing the coating, pure acrylic emulsion B of equal mass is used to replace pure acrylic emulsion A in Example 1, that is, the coating only uses pure acrylic emulsion B. And by adjusting the feeding amount of oxidizing and aqueous solvents, the raw materials include 2 parts of zinc oxide. The rest of the raw material ratios and preparation methods are strictly consistent with Example 1.
[0083] Comparative Example 7
[0084] This comparative example refers to the preparation method provided in Example 1 to prepare a coating. The difference between this comparative example and Example 1 is that in the process of preparing the coating, pure acrylic emulsion B of equal mass is used to replace pure acrylic emulsion A in Example 1, that is, the coating only uses pure acrylic emulsion B. And by adjusting the feeding amount of oxidizing and aqueous solvents, 10 parts of zinc oxide are included in the raw materials. The rest of the raw material ratios and preparation methods are strictly consistent with Example 1.
[0085] Test Example 2
[0086] Test objects: the exposed high-strength single-component waterproof coating provided in Examples 5 to 7 and the coating provided in Comparative Examples 5 to 7.
[0087] Test items and methods:
[0088] (1) Tensile properties: The tensile properties test method in this test example is consistent with the tensile properties test method used in Test Example 1.
[0089] (2) Tensile properties after artificial weathering: The method for testing the tensile properties after artificial weathering in this test example is consistent with the method for testing the tensile properties after artificial weathering used in Test Example 1.
[0090] Test results: The test results of the above tests are shown in Table 5.
[0091] Table 5. Test properties of coatings prepared by each test object
[0092]
[0093] Result analysis:
[0094] By comparing the coatings and performance indicators provided by Example 1 with those provided by Examples 5 to 7, it can be found that the tensile strength of the coatings provided by Examples 1 and 5 to 7 before aging treatment both reached 2.72Mpa or above; and when the coating includes pure acrylic emulsion A and pure acrylic emulsion B, as the amount of zinc oxide in the coating increases, the tensile strength of the coating formed by the coating (untreated) shows an upward trend, and the elongation at break of the coating (untreated) shows a downward trend. Similarly, by comparing the coatings and performance indicators provided by Comparative Example 2 with those provided by Comparative Examples 5 to 7, it can be found that the tensile strength of the coatings provided by Comparative Example 2 and Comparative Examples 5 to 7 before aging treatment both do not reach 2.72Mpa or above; and when the coating includes only pure acrylic emulsion B, as the amount of zinc oxide in the coating increases, the tensile strength of the coating formed by the coating (untreated) also shows an upward trend, and the elongation at break of the coating (untreated) also shows a downward trend.
[0095] However, by comparing the tensile strength and elongation at break of the coatings of Example 1, Examples 5 to 7 with Comparative Examples 2 and Comparative Examples 5 to 7 before aging treatment, it can be found that when the same amount of zinc oxide is introduced into the coating, the coating including both pure acrylic emulsion A and pure acrylic emulsion B has a greater change in tensile strength and elongation at break than the coating using only pure acrylic emulsion B. That is to say, in the coatings provided in Example 1 and Examples 5 to 7, there is a synergistic effect between zinc oxide and pure acrylic emulsion A and pure acrylic emulsion B, which can improve the toughness and strength of the coating.
[0096] The above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the protection scope of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A high-strength single-component waterproof coating that can be exposed, characterized in that: Calculated by weight, the raw materials for preparing the exposed high-strength single-component waterproof coating include: 350 to 450 parts of pure acrylic emulsion A, 150 to 250 parts of pure acrylic emulsion B, 250 to 350 parts of powder, 13.5 to 39 parts of additives, and 50 to 110 parts of aqueous solvent; Among them, the glass transition temperature of pure acrylic emulsion A is -10℃~0℃, and the glass transition temperature of pure acrylic emulsion B is -45℃~-30℃.
2. The high-strength single-component waterproof coating as claimed in claim 1, characterized in that: The pure acrylic emulsion A comprises an organosilicon-modified pure acrylic emulsion, and the organosilicon content of the organosilicon-modified pure acrylic emulsion is 1-2 wt %.
3. The high-strength single-component waterproof coating as claimed in claim 1, characterized in that: Calculated by weight, the auxiliary agent includes 2 to 10 parts of zinc oxide.
4. The high-strength single-component waterproof coating as claimed in claim 1, characterized in that: The pH value of the exposed high-strength single-component waterproof coating is 7.5-8.
5.
5. The high-strength single-component waterproof coating as claimed in claim 1, characterized in that: The powder includes at least one of calcium carbonate, barium sulfate, titanium dioxide and talcum powder.
6. The high-strength single-component waterproof coating as claimed in claim 5, characterized in that: Calculated by weight, the auxiliary agent includes 0.5 to 1.5 parts of cellulose ether.
7. The high-strength single-component waterproof coating as claimed in claim 6, characterized in that: The cellulose ether is hydrophobically modified hydroxyethyl cellulose ether.
8. The high-strength single-component waterproof coating as claimed in claim 1, characterized in that: Calculated by weight, the auxiliary agent includes 2 to 6 parts of sodium salt dispersant.
9. The high-strength single-component waterproof coating as claimed in claim 1, characterized in that: Calculated by weight, the auxiliary agent includes 1 to 5 parts of a plasticizer, and the plasticizer includes at least one of phthalate and aliphatic dibasic acid ester.
10. A method for preparing the high-strength single-component waterproof coating as claimed in any one of claims 1 to 9, characterized in that: The following operations are included: Firstly, the pure acrylic emulsion A and the pure acrylic emulsion B are mixed with the aqueous solvent to obtain a premixed liquid, and then the premixed liquid is mixed with the remaining raw materials to obtain the exposed high-strength single-component waterproof coating.
Citation Information
Patent Citations
Aqueous organosilicon modified acrylic acid primer-topcoat vehicle axle coating and preparation method thereof
CN107267003A
High-strength and high-water-resistance polymer emulsion building waterproof coating and preparation method thereof
CN109135460A
Roof waterproofing material
CN110272652A
Water-based sound-insulation heat-preservation elastic waterproof coating and preparation method thereof
CN113444412A